Pengaruh Liquidity Management terhadap Kinerja Keuangan pada Perbankan Konvensional yang Terdaftar di Bursa Efek Indonesia - Serly Permatasari; Deany Putri Aprilia; Henny Setyo Lestari (Universitas Batanghari, 2022)
The purpose of this research is to look at the factors that influence liquidity control and performance of conventional banking companies in Indonesia. The banking industry is one of the sectors with relatively high growth and liquidity is one of the determinants of a bank's performance as measured by the help of ROA, ROE. The sampling method used purposive sampling with certain company criteria. The sample includes 45 conventional banking companies. The data used is secondary data originating from the Indonesia Stock Exchange (IDX). Data taken in 2016-2020 using certain statistical techniques, namely descriptive statistics, correlations, and regression analysis. The results showed that the current ratio, quick ratio, and capital ratio had no effect on financial performance (ROA), while the liquid assets ratio had no effect on financial performance (ROA). The current ratio, quick ratio, has no effect on financial performance (ROE), while the capital ratio and liquid assets ratio affect financial performance (ROE).